Prophylactic corticosteroid to prevent pain flare in bone metastases treated by radiotherapy - Viani, Gustavo Arruda (Rep Pract Oncol Radiother, 2021)
BACKGROUND: The aim of this study was to evaluate the effectiveness of prophylactic corticosteroids to prevent pain flare (PF) in bone metastases treated with radiotherapy performing a meta-analysis of randomized clinical trials (RCT). MATERIALS AND METHODS: RCTs were identified on Medline, Embase, the Cochrane Library, and the proceedings of annual meetings through June 2020. We followed the PRISMA and MOOSE guidelines. A meta-analysis was performed to assess if corticosteroids reduce the PF, pain progression, and the mean of days with PF compared with the placebo. A p-value < 0.05 was considered significant. RESULTS: Three RCTs with a total of 713 patients treated were included. The corticosteroids reduced the occurrence of early PF 20.5% (51/248) versus 32% (80/250) placebo, OR = 0.55 (95% CI: 0.36–0.82, p = 0.002). The mean days of PF were reduced to 1.6 days (95% CI: 1.3–1.9, p = 0.0001). Prophylactic corticosteroids had more patients with no PF and no pain progression, OR = 1.63 (95% CI: 1.14–2.32, p = 0.007). No significant corticosteroids effect was observed for pain progression (p = ns) and late PF occurrence (p = ns). CONCLUSION: Prophylactic corticosteroids reduced the incidence of early PF, the days with PF, resulting in a superior rate of patients with no PF and no pain progression, but with no significant benefit for reducing pain progression or late PF occurrence.